Catalytic hydrogenation - Červený, L. (Studies in surface science and catalysis ;, 1986)
The collection of contributions in this volume presents the most up-to-date findings in catalytic hydrogenation. The individual chapters have been written by 36 top specialists each of whom has achieved a remarkable depth of coverage when dealing with his particular topic. In addition to detailed treatment of the most recent problems connected with catalytic hydrogenations, the book also contains a number of previously unpublished results obtained either by the authors themselves or within the organizations to which they are affiliated. Because of its topical and original character, the book provides a wealth of information which will be invaluable not only to researchers and technicians dealing with hydrogenation, but also to all those concerned with homogeneous and heterogeneous catalysis, organic technology, petrochemistry and chemical engineering.